2020
DOI: 10.3390/ijms21239091
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Biliverdin Reductase-A Expression in Visceral Adipose Tissue is Associated with Adipocyte Dysfunction and NAFLD in Human Obesity

Abstract: Biliverdin reductase A (BVR-A) is an enzyme involved in the regulation of insulin signalling. Knockout (KO) mice for hepatic BVR-A, on a high-fat diet, develop more severe glucose impairment and hepato-steatosis than the wild type, whereas loss of adipocyte BVR-A is associated with increased visceral adipose tissue (VAT) inflammation and adipocyte size. However, BVR-A expression in human VAT has not been investigated. We evaluated BVR-A mRNA expression levels by real-time PCR in the intra-operative omental bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…The loss of adipocyte BVRA also decreases insulin signaling in white adipose tissue contributing to increased fasting hyperglycemia in knockout mice [ 127 ]. These results agree with the finding from obese human patients who exhibit lower levels of BVRA, increased levels of inflammation, and increased adipocyte size [ 128 ]. CRISPR knockout of BVRA in hepatocytes and kidney proximal tubules cells induces oxidative stress and lipid accumulation [ 124 , 125 ].…”
Section: The Signaling Mechanisms Of Heme Oxygenase and Bilirubin In ...supporting
confidence: 92%
See 1 more Smart Citation
“…The loss of adipocyte BVRA also decreases insulin signaling in white adipose tissue contributing to increased fasting hyperglycemia in knockout mice [ 127 ]. These results agree with the finding from obese human patients who exhibit lower levels of BVRA, increased levels of inflammation, and increased adipocyte size [ 128 ]. CRISPR knockout of BVRA in hepatocytes and kidney proximal tubules cells induces oxidative stress and lipid accumulation [ 124 , 125 ].…”
Section: The Signaling Mechanisms Of Heme Oxygenase and Bilirubin In ...supporting
confidence: 92%
“…The loss of hepatocyte BVRA increases activation of glycogen synthase kinase 3beta (GSK3β) via decreased levels of serine 9 (Ser9) phosphorylation which in turn increases serine 73 (Ser73) phosphorylation of PPARα, increasing protein turnover and decreasing its transcriptional activity [ 50 ]. Interestingly, reduced adipocyte levels in BVRA in obese human patients resulted in significantly more hepatic steatosis and NAFLD [ 128 ]. These results suggest that BVRA can have both direct and indirect effects to contribute to hepatic steatosis and the development of NAFLD.…”
Section: The Signaling Mechanisms Of Heme Oxygenase and Bilirubin In ...mentioning
confidence: 99%
“…NAFLD is a typical heterogeneous disease involving multiple pathogenic pathways [38]. One dominant theory proposes that accumulated triglycerides induce cellular damage caused by oxidative stress, protein misfolding, mitochondrial damage, and endoplasmic reticulum stress responses [39], leading to a persistent state of chronic inflammation that directs body tissue toward immunity and inflammation overactivation [40]. It has been suggested that both innate and adaptive immune activation can further 2…”
Section: Introductionmentioning
confidence: 99%
“…TLR2 has been proven to be greatly involved in NASH inflammation either by activating Kupffer cell inflammasome or forming heterodimers with TLR6 on recognizing gram-positive diacylated lipopeptides. The animal model with dysfunctional TLR2 did not develop expected insulin resistance and proinflammatory surge when diet-mediated NASH was induced [10]. The continued exposure to dysbiosis not just boosts NAFLD to NASH but the compositional change in microorganisms' surface molecules increases the delivery of new and robust TLRs to the liver, further enhancing the inflammatory soar.…”
Section: The Role Of Tlrsmentioning
confidence: 96%
“…At the outset, the accumulated triglycerides induce cell injury secondary to oxidative stress, modified metabolism, protein misfolding, mitochondrial damage, and endoplasmic reticulum stress response creating a persistent chronic systemic inflammation state [8,9]. The continuous high-fat diet and energy imbalance results in adipose tissue hyperplasia and hypertrophy with altered hormonal and enzymatic activity directing body hemostasis towards immune and inflammatory overactivity [10].…”
Section: Introductionmentioning
confidence: 99%